The Jesus of Orthodoxy and the Jesuses of the Gospels: a Critique of Luke Timothy Johnson's the Real Jesus - Miller, Robert J. (1998)
A central thesis of L.T. Johnson's The Real Jesus is that the gospels manifest a uniform pattern that discloses the meaning of Jesus' life and death and the paradigm of discipleship. This pattern, Johnson claims, is the same in all four gospels. This essay demonstrates that Johnson's thesis is wrong. I argue that the gospels have dis tinctive patterns that differ significantly from one another. Furthermore, no one gospel actually contains the pattern Johnson describes. Johnson's uniform pattern depends on a selectivity that suppresses contrary evidence and ignores the integrity and dis tinctiveness of the individual gospels.Johnson also contends that the historical Jesus is irrelevant to Christian faith, which must be directed toward the risen Christ. However, by asserting that the gospel pattern he proposes is 'embedded in the earliest Christian experience and memory', Johnson covertly appeals to the historical Jesus as the authoritative grounding for the object of Christian faith.